2021
DOI: 10.1016/j.bios.2021.113134
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex quantitative detection of SARS-CoV-2 specific IgG and IgM antibodies based on DNA-assisted nanopore sensing

Abstract: The coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread into a global pandemic. Early and accurate diagnosis and quarantine remain the most effective mitigation strategy. Although reverse transcriptase polymerase chain reaction (RT-qPCR) is the gold standard for COVID-19 diagnosis, recent studies suggest that nucleic acids were undetectable in a significant number of cases with clinical features of COVID-19. Serologic assays that detect human antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 64 publications
(53 reference statements)
0
37
0
2
Order By: Relevance
“…Several studies showed that the IgG concentration ranged between 1.4 and 4200 μg/mL in COVID-19 patients' serum, and the neutralization antibodies concentration should be higher than 1.0 μg/mL to ensure the effective protection [ [27] , [28] , [29] , [30] ]. Therefore, the sensitivity of the OPOCT is adequate for detecting S-IgG in COVID-19 patients’ serum, and was also comparable to those of other immunoassays [ 12 , 20 , 27 , [31] , [32] , [33] , [34] , [35] ] ( Table S1 ). Compared with the reported works, our method can achieve quantitative detection of IgG with high sensitivity (LOD = 12.5 ng/mL) and relatively short assay time (about 25 min).…”
Section: Resultsmentioning
confidence: 55%
“…Several studies showed that the IgG concentration ranged between 1.4 and 4200 μg/mL in COVID-19 patients' serum, and the neutralization antibodies concentration should be higher than 1.0 μg/mL to ensure the effective protection [ [27] , [28] , [29] , [30] ]. Therefore, the sensitivity of the OPOCT is adequate for detecting S-IgG in COVID-19 patients’ serum, and was also comparable to those of other immunoassays [ 12 , 20 , 27 , [31] , [32] , [33] , [34] , [35] ] ( Table S1 ). Compared with the reported works, our method can achieve quantitative detection of IgG with high sensitivity (LOD = 12.5 ng/mL) and relatively short assay time (about 25 min).…”
Section: Resultsmentioning
confidence: 55%
“…Targeting rapid and sensitive COVID-19 serology testing at the point of care (POC), a variety of portable immunosensing platforms have been developed based on microfluidics and biosensor technologies ( Fabiani et al, 2021 ; Kim et al, 2021a ; Lee et al, 2021 ; Li et al, 2021 ; Raziq et al, 2021 ; Roda et al, 2021 ; Tan et al, 2020a ; Torrente-Rodríguez et al, 2020 ; Yakoh et al, 2021 ; Zakashansky et al, 2021 ; C. Zhang et al, 2021 ; Z. Zhang et al, 2021 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 7 Although RT-PCR is a current standard method for SARS-CoV-2 diagnosis due to its high precision and specificity, 8 , 9 some data indicate that this detection technique is not suitable for all cases with clinical features of SARS-CoV-2, and serologic assay has become an indispensable tool as a complementary method for accurate diagnosis. 10 In serologic assay, commercially available ELISA is considered as a reliable detection method, but its efficiency is limited by laborious and time-consuming operation. Although a GICA-based method is convenient and time-saving for SARS-CoV-2 detection, its low detection sensitivity is not satisfactory for early and prompt screening of this disease.…”
Section: Introductionmentioning
confidence: 99%